RESPONSIBLE APPROACH TO THE DEVELOPMENT OF REHABILITATION EDUCATION: EFFECTIVE PARTNERSHIP AND COLLABORATION OF THE INITIATIVE «REHABILITATION OF WAR TRAUMA IN UKRAINE» - Boichuk, Anastasiia; Yezhova, Olha; Baryshok, Tetiana; Timchenko, Polina; Baran, Oksana; Kumka, Antonina; Ivanenko, Inna; Tymruk-Skoropad, Kateryna (Eastern Ukrainian Medical Journal, 2025)
Objective of the study was to analyse the results of applying a responsible approach to the development of rehabilitation education through partnership and collaboration within the framework of the Ukrainian-Swiss initiative «Rehabilitation of War Trauma in Ukraine » (RWT).Methods. The scientific study employed theoretical, empirical, and statistical methods. A survey of physical therapists and university faculty members was conducted using a specially designed questionnaire consisting of three sections: general, for participants, and for prospective participants of the RWT initiative events. The survey involved 120 respondents from different regions of the country, 82.5% of whom had participated in educational activities of the initiative.Results. The main goal of the RWT initiative’s «Strengthening Rehabilitation Education» direction is to achieve positive, sustainable, and systemic changes through education, leading to an overall improvement in the rehabilitation system. This goal is ensured by the consistent development of interconnected activities that form the foundation for future initiatives, the implementation of integrated solutions, and the expansion of cooperation through partnerships and collaborations with partners and stakeholders who share common values.The «Strengthening Rehabilitation Education» direction primarily focused on the development of undergraduate education and continuous professional development for both rehabilitation specialists and university educators. Within the framework of the Ukrainian-Swiss initiative, educational and methodological support was developed for five educational components for the «Therapy and Rehabilitation» specialty; a series of webinars by the Ministry of Health of Ukraine was conducted; and various training sessions on different topics were developed and implemented.The survey results indicated that most respondents attended training sessions and courses on rehabilitation management. Over 34% of respondents had experience participating in national professional community events such as congresses and/or conferences. Specialized educational programs involved 26.7% of respondents, while training sessions on management and communication in rehabilitation engaged 17.8%. Events aimed at professional community development were attended by 8.9% of respondents. The quality of events was rated as «excellent» by 83% of respondents and «very good» by 15.2%, with 53.8% considering the content relevant and useful. The key advantages highlighted by participants included the professionalism and high level of speakers (28.6%), opportunities for experience exchange and effective communication (25.3%), and hands-on skill development (24.2%).Conclusions. The application of a responsible approach through collaboration and partnership within the Ukrainian-Swiss RWT initiative has yielded results that have continued systemic changes in domestic rehabilitation education. It has been proven that effective forms of collaboration include the creation of working groups consisting of physical therapists and university faculty to achieve specific objectives, consultation and training with leading international experts, and the implementation of various educational activities. Additionally, international initiatives and projects have been identified as effective forms of partnership.